First-ever study uncovers microplastic contamination in Nepalese table salt - Kishor Kumar Maharjan; Ram Prasad Dhungel (Heliyon, 2024)
Despite numerous studies on microplastic contamination in table salt worldwide, research focusing on Nepalese table salts is remarkably lacking. This study aims to address this gap by investigating microplastic contamination in salt samples collected from all seven provincial zones of Nepal. Our objective is to comprehensively assess the presence and characteristics of microplastics in salt sold within local markets across the country. Five salt packaging companies utilized by Nepalese consumers were identified. The collected salt samples were digested with Fenton's reagent to extract microplastics, which were then observed under a digital microscope. Using an OMAX stereomicroscope at 30× magnification and an OMAX A3503S digital camera, each microplastic was carefully identified and quantified. FTIR analysis was conducted to identify the polymer types. All tested salt samples (100 %) from both Nepalese and Indian packaging companies contained microplastics. Microplastic abundance exhibits variability among the samples, ranging from 80 to 1040 microplastics per kilogram of salt. The average value stands at 381 ± 219 microplastics per kilogram of salt sample. The distribution of microplastic concentrations within the salt samples reveals that the majority fall within the 301–400 microplastics per kilogram salt range, constituting 33 % of the total samples. Color analysis showed diverse contamination sources, while microplastic shapes included fibers (56 %), films (17 %), fragments (16 %) and pellets (11 %). Polymer type analysis confirmed the presence of polyethylene and polypropylene in tested microplastics. The study estimated that Nepalese individuals ingest an average of 1853 microplastics annually, indicating significant exposure from salt consumption. Surprisingly, factors such as storage conditions, date of salt packaging and thickness of packaging material did not significantly affect microplastic presence in the samples, suspecting manufacturing processes as the primary contributors to contamination. Therefore, the raw materials and purification practices for salt need improvement, as existing methods are insufficient to eliminate microplastics. These findings emphasize the need for further research and mitigation efforts to address microplastic contamination in Nepalese salt and its potential health impacts.